Relationships of automatic associations, affect, and outcome expectations with adolescents' impulsive decision to opt into physical activity. Issue 6 (2nd November 2022) - McFadden, Kimberley; Berry, Tanya; McHugh, Tara-Leigh; Rodgers, Wendy
ABSTRACT: This quasi-experimental study examined whether adolescents' health and social/appearance automatic associations for physical activity (PA) and the self-reported psychosocial variables of outcome expectations, self-efficacy, and positive body image predicted their impulsive decision to opt into a hypothetical PA programme. Eighty high school students (15.84 ± 1.12 years; 47.5% female) were cluster random assigned by classroom to one of two groups. All participants completed two automatic association tasks followed by a questionnaire about their outcome expectations of PA, self-efficacy for exercise, positive body image, and PA behaviour. Participant groups then received a presentation about a hypothetical programme that emphasised either individualised, health-focused PA ( n = 39) or group, social-focused PA ( n = 41). Participants were pressured to provide a rapid, impulsive response regarding interest in participation. Participants automatically associated positive health words and positive social/appearance words with PA. There was a significant difference between groups in their responses to the hypothetical PA programme; participants who received the health-focused PA description were 3.59 times more likely to opt into the programme than those who received the social-focused PA description. Furthermore, positive automatic health associations and higher expectations of stress management outcomes predicted impulsively opting into the PA programme. Adolescents automatically associate both positive health outcomes and positive social/appearance outcomes with PA. Automatic health associations and stress management outcome expectations were predictors of opting into PA. Presenting PA as an opportunity to focus on one's individual fitness goals and the health benefits, particularly the stress-reducing effects, of PA may increase adolescent PA participation.